Behaviour and production traits correlation of five breeds of sheep - Handiwirawan, Eko; Noor, R.R; Sumantri, C; ., Subandriyo (Indonesian Animal Sciences Society, 2012)
Information about correlations among behavioral traits and production traits may facilitate using easily measured traits to be used as alternative criteria for indirect selection to improve other traits in sheep. The purpose of this study was to estimate correlations among behavioral and production traits of five breeds of sheep.Â A total of 128 head of weaned lambs and 168 ewes with nursing lambs of five breeds were used in this study, i.e. Barbados Black Belly Cross (BC), Composite Garut (KG), Local Garut (LG), Composite Sumatra (KS) and St. Croix Cross (SC). Temperament was assessed in a test arena, for subsequent association with growth rate and ewe productivity. Analysis of variance of production and behavioral traits among breeds was carried out using PROC GLM of SAS software Ver. 9.0.Â PROCCORR was used to estimate correlations among production and behavioral variables. Weaned lambs that were more docile towards the observer had higher daily gains.Â Ewes that bleated more frequently when separated from their lamb had higher lamb weaning weights and lamb survival than ewes bleating fewer times under the same conditions. In BC ewes, a positive correlation was observed between frequency of bleats and lamb survival. Key Words: Sheep, Behavior, Growth rate, Ewe productivity